Vaccination strategy for epidemic viral diseases in healthcare workers: Cut-off for optimal immunization. Issue 1 (January 2019) - Yoshioka, Nori; Deguchi, Matsuo; Hagiya, Hideharu; Kagita, Masanori; Tsukamoto, Hiroko; Takao, Miyuki; Tomono, Kazunori
Abstract: Healthcare workers (HCWs) are at an increased risk of being exposed to epidemic viral diseases (EVDs), such as measles, rubella, mumps, and varicella-zoster. Currently, in case of the absence of written records on previous immunizations, the Japanese Society for Infection Prevention and Control guidelines require HCWs to have antibody titers higher than laboratory thresholds, possibly leading to over-immunization. We report our vaccination strategy and the consequent incidences of EVDs at the Osaka University Hospital between 2000 and 2016. In 2001, we initiated an annual serology check of antibody titers against EVDs and immunization for newly employed HCWs. As an additional vaccination program, all HCWs with low antibody titers were vaccinated in 2005 and 2010. Antibody titers were determined by an enzyme immunoassay (EIA), with a positive range of >2.0 cut-off index. After implementing the vaccination strategy to keep the laboratory threshold, there were only sporadic cases of EVDs among HCWs. More than 99% of individuals who had positive titers in 2005 remained the positive antibody titers in 2010, indicating that a minimum interval of 5 years is enough to measure immunity. Unprotected workers can, even silently, transmit the contagious viruses to patients and coworkers, possibly resulting in a nosocomial outbreak. However, over-vaccination may yield adverse effects and financial burdens. Our observational data indicate that the laboratory cut-off index of >2.0 by EIA may provide a sufficient herd immunity to prevent EVDs among HCWs.